Analysis of operation and emission characteristics of refrigerated-vehicles based on remote technology - Xionghui Zou; Yanyan Yang; Zhengjun Yang; Jingyuan Li; Yu Liu; Yang Lu; Qian Feng (Heliyon)
Remote online monitoring technology is an effective method for tracking in-use diesel vehicles. Based on remote data from the OBD system, this study compares and analyzes the operation characteristic, emissions and fuel consumption of light-, medium-, and heavy-duty refrigerated diesel vehicles for a year. The results indicate that the average idle ratio of refrigerated vehicles is higher than the average value in the 5 speed intervals ranging from 0 to 50 km/h, serving as a pivotal factor that influences total emissions and energy consumption. The NOx emission factors of vehicles are higher in winter and summer compared to other seasons. The annual average NOx emission factor for heavy-duty refrigerated vehicles is 0.232 g/km, which is 45 % higher than that of medium-duty vehicles and 54.7 % higher than that of light-duty vehicles. The urea levels of light-, medium-, and heavy-duty vehicles decreased by approximately 3 %–5 % per 100 km, and this trend in urea consumption paralleled the monthly variations in vehicle fuel consumption.